A Comprehensive Review on the Nanocarrier-based Drug Delivery of Cabazitaxel (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Drug resistance significantly impacts the anticancer activity of several taxane-based formulations, i.e., docetaxel (DTX) and paclitaxel (PTX) formulations in clinical research. Cabazitaxel is a second-generation taxane with high anticancer efficacy than paclitaxel and docetaxel. The structure of cabazitaxel depicts low P-glycoprotein (p-gp) efflux pump affinity, which could help overcome the taxane resistance. Cabazitaxel’s clinical use is limited to metastatic castration-resistant prostate cancer (mCRPC) who have progressed after the chemotherapy from the docetaxel because of its hydrophobicity and high toxicity as the less stability of its marketed formulation, Jevtana®. The nanomedicines of cabazitaxel have the potential to overcome the constraints of drug use and overcome taxane resistance. This review reports on the recent cabazitaxel-based drug delivery systems, explains the obstacles encountered in creating cabazitaxel nanoformulations and provides solutions to address these challenges.